The Impact of the Russo-Ukrainian War on Sino-German Relations - Mohd Sani, Mohd Azizuddin; Ehret, Marian (National Sun Yat-sen University, 2022)
This paper investigates how Sino-German relations would be impacted by the Russo-Ukrainian War of 2022. The relations between both Eurasian partners were found to be significantly influenced by US-German relations. The theory of Historical Cycles by cultural philosopher Oswald Spengler was used as an analytical tool. As a consequence of the war, findings suggested a far-reaching, permanent decline of Germany's industrial-financial base until the 2030s. A potential Trump government could facilitate such a result. Also triggered by the war, Berlin would predominantly act in alignment with an American lead - Beijing and Berlin's strategic partnership could fail. While China and Russia would most likely stay free of America's influence, Washington would probably be able to dominate Germany, Europe, the West, and perhaps most of the world.